2003
DOI: 10.1094/phyto.2003.93.4.493
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Quantitative Field Resistance Against Apple Scab in a ‘Fiesta’ × ‘Discovery’ Progeny

Abstract: Breeding of resistant apple cultivars (Malus x domestica) as a disease management strategy relies on the knowledge and understanding of the underlying genetics. The availability of molecular markers and genetic linkage maps enables the detection and the analysis of major resistance genes as well as of quantitative trait loci (QTL) contributing to the resistance of a genotype. Such a genetic linkage map was constructed, based on a segregating population of the cross between apple cvs. Fiesta (syn. Red Pippin) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
1
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 36 publications
4
48
1
1
Order By: Relevance
“…However, a lot of strains were avirulent to 'Discovery' and virulent to 'Golden', showing that 'Discovery' possesses some additional resistance factors; this could explain why only 20% of the strains were virulent to Discovery. These results are concordant with those obtained by Liebhard et al (2003) and Calenge et al (2004), mapping the resistance to scab in two progenies of 'Discovery'. Sixty-seven percent of the strains were virulent to 'Fiesta'.…”
Section: Constitution Of the Core-collection Of V Inaequalissupporting
confidence: 90%
“…However, a lot of strains were avirulent to 'Discovery' and virulent to 'Golden', showing that 'Discovery' possesses some additional resistance factors; this could explain why only 20% of the strains were virulent to Discovery. These results are concordant with those obtained by Liebhard et al (2003) and Calenge et al (2004), mapping the resistance to scab in two progenies of 'Discovery'. Sixty-seven percent of the strains were virulent to 'Fiesta'.…”
Section: Constitution Of the Core-collection Of V Inaequalissupporting
confidence: 90%
“…SSR-based maps have been essential for identification and positional comparison of major genes and QTLs for scab, powdery mildew, and fire blight resistance (Durel et al , 2003Evans and James 2003;Liebhard et al 2003c;Calenge et al 2004;Gygax et al 2004;James et al 2004;Patocchi et al 2004;Tartarini et al 2004;Vinatzer et al 2004;Khan et al 2006) as well as morphological or physiological traits (Conner et al 1998;King et al 2000;Liebhard et al 2003a;Costa et al 2005). Recognition of SSR associations led to the identification of clusters of resistance genes (e.g., Bus et al 2004) and to the first integrated map of apple that reviews many papers with regard to the location of scab resistance genes .…”
Section: Introductionmentioning
confidence: 99%
“…2 and Va from PI 172623 (Williams and Kuc 1969;Lespinasse 1989). All except Va have already been introduced into breeding lines, making them available for breeding purposes (Liebhard et al 2003). However, molecular markers are available for Vf, Vm (Cheng et al 1998), Vbj (Gygax 2004), Vr (Hemmat et al 2002 and for a second resistance gene, Vx, recently identified in Russian seedling (Hemmat et al 2002).…”
Section: Introductionmentioning
confidence: 99%